Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
[tex]9-7x=(4x-3)^2+5 \\
9-7x=16x^2-24x+9+5 \\
9-7x=16x^2-24x+14 \\
0=16x^2-24x+14-9+7x \\
0=16x^2-17x+5 \\
\boxed{16x^2-17x+5=0} \\
\hbox{answer D}[/tex]
Answer:
Option D - [tex]16x^2-17x + 5=0[/tex]
Step-by-step explanation:
Given : Expression [tex]9 - 7x = (4x - 3)^2 + 5[/tex]
To find : Which shows the equation below written in standard form?
Solution :
Step 1 - Write the expression
[tex]9 - 7x = (4x - 3)^2 + 5[/tex]
Step 2 - Solve the square term
[tex]9 - 7x = 16x^2+9-24x + 5[/tex]
Step 3 - Place like term together
[tex]16x^2-24x+7x + 5+9-9=0[/tex]
[tex]16x^2-17x + 5=0[/tex]
Therefore, Option D is correct.
The standard form of the equation is [tex]16x^2-17x + 5=0[/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.